PGPR activity of coal solubilizing bacteria - Brito-Campo, Helen; Ayala-Santamaría, María; Barros-Escalante, Katherin; Cubillos-Hinojosa, Juan; Pantoja-Guerra, Manuel; Osvaldo Valero, Nelson; Gómez Gómez, Liliana (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
Coal solubilizing bacteria (CSB) are microorganisms to able to bio transformed low rank coal, releasing humified organic matter in the process. On the other hand, these bacterial genera have reported previously as plant growth promoting bacteria. The aim of this work was to assess the Plant Growth Promoting Rhizobacteria (PGPR) capacity of five CSB strains: Bacillus pumilus (CSB05), B. mycoides (CSB25), Microbacterium sp. (CSB3), Acinetobacter sp. (CSB13) and B. amyloliquefaciens (CSB02). For this, the PGPR traits of CSB were evaluated under laboratory conditions: the biological nitrogen fixation capacity, the reduction of acetylene, the synthesis of indole acetic acid (IAA) and the solubilization of phosphates. In a second experiment under plant nursery conditions, PGPR activity of strain CSB05 was evaluated in common bean plants. Under laboratory conditions, it was evidenced that all the evaluated strains produced IAA, solubilized phosphate in a liquid medium, presented atmospheric nitrogen fixation capacity, and only the CSB3 and CSB13 strains reduced acetylene. In the plant nursery experiment, PGPR activity of strain CSB05 was detected in common bean plants, reflected in increases in the height of these plants. These results show that CSB are promising in the PGPR activity, which is interesting to the design of biological products with agricultural and environmental applications, for the management of crops in disturbed soils of the Colombian dry Caribbean.